Catalytic co-pyrolysis of Alternanthera philoxeroides and peanut soapstock via a new continuous fast microwave pyrolysis system. (1st April 2019) - Wang, Yunpu; Tian, Xiaojie; Zeng, Zihong; Dai, Leilei; Zhang, Shumei; Jiang, Lin; Wu, Qiuhao; Yang, Xiuhua; Liu, Yuhuan; Zhang, Bo; Yu, Zhenting; Wen, Pingwei; et al.
Graphical abstract: Highlights: A continuous fast microwave pyrolysis system was used for pyrolysis. The optimal catalytic and co-pyrolysis parameters were determined. It is proved that the soapstock and A. philoxeroides have synergies in pyrolysis. Abstract: Continuous fast microwave catalytic co-pyrolysis of Alternanthera philoxeroides and peanut soapstock was studied using HZSM-5 as catalyst. The effects of catalyst temperature, feedstock-to-catalyst ratio, and A. philoxeroides -to-peanut soapstock ratio on the yield and composition of bio-oil were studied. Experimental results showed that the optimum catalyst temperature was 400 °C. The catalyst increased the proportion of aromatics but reduced the bio-oil yield. The optimum feedstock-to-catalyst ratio was 2:1. A. philoxeroides presented a significant synergistic effect with peanut soapstock, which facilitated the production of aromatics in the bio-oil. The optimum A. philoxeroides -to-peanut soapstock ratio was 1:2.